2015
DOI: 10.1002/ejic.201403228
|View full text |Cite
|
Sign up to set email alerts
|

Heteroleptic Phenanthroline Complexes of Trinuclear Molybdenum Clusters with Luminescent Properties

Abstract: Registro de acceso restringido Este recurso no está disponible en acceso abierto por política de la editorial. No obstante, se puede acceder al texto completo desde la Universitat Jaume I o si el usuario cuenta con suscripción. Registre d'accés restringit Aquest recurs no està disponible en accés obert per política de l'editorial. No obstant això, es pot accedir al text complet des de la Universitat Jaume I o si l'usuari compta amb subscripció. Restricted access item This item isn't open access because of publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…[2] In particular,m olybdenum and tungsten sulfides, including triangular clusters, were reportedt ob ee fficient electrocatalysts for the generation of hydrogen. [3][4][5][6][7][8][9][10][11] Jaramillo et al reported the hydrogen evolution reaction(HER) of the Mo IV [Mo 3 S 4 (H 2 O) 9 ] 4 + clusterc omplex supported on highly oriented pyrolytic graphite (HOPG) under electrochemical conditions, and ah igh turnover frequency (TOF) value (0.07 s À1 )p er cluster molecule wasa chieved. [12] Other molybdenum-sulfur and tungsten-sulfur complexes were studied in the HER under photochemical conditions, for which the presence of ap hotosensitizer and as acrificial donor is needed.…”
Section: Introductionmentioning
confidence: 99%
“…[2] In particular,m olybdenum and tungsten sulfides, including triangular clusters, were reportedt ob ee fficient electrocatalysts for the generation of hydrogen. [3][4][5][6][7][8][9][10][11] Jaramillo et al reported the hydrogen evolution reaction(HER) of the Mo IV [Mo 3 S 4 (H 2 O) 9 ] 4 + clusterc omplex supported on highly oriented pyrolytic graphite (HOPG) under electrochemical conditions, and ah igh turnover frequency (TOF) value (0.07 s À1 )p er cluster molecule wasa chieved. [12] Other molybdenum-sulfur and tungsten-sulfur complexes were studied in the HER under photochemical conditions, for which the presence of ap hotosensitizer and as acrificial donor is needed.…”
Section: Introductionmentioning
confidence: 99%
“…An analysis of noncovalent interactions in compounds of metals and bioorganic molecules can provide valuable data on the properties of compounds, in terms of recognition processes 5 and receptor-information chains, 6 the influence of co-factors, 7 and also for the interpretation of intermolecular energy transfer processes. 8 Even weak intermolecular interactions affect the properties such as luminescence, 9,10 solubility in different solvents, 11 phase transition temperature 12 and type.…”
Section: Introductionmentioning
confidence: 99%